Pengaruh Minat dan Motivasi Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS kelas VIII SMP Negeri 6 Singaraja - Ginting, Winata Ekelninta; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to determine the influence of partial and simultaneous learning interest and motivation on student learning outcomes. The type of research used is causal-type quantitative research. The sampling technique used is a probability sampling technique with simple random sampling. The sample for this research was class VIII students at SMP Negeri 6 Singaraja, with a total sample of 181 students. The data collection method uses a questionnaire and is analyzed using multiple linear regression. Instrument testing was carried out using validity and reliability tests. The classical assumption tests used are the normality test, multicollinearity test, and heteroscedasticity test. The research results show that (1) there is a positive and significant influence of interest on student learning outcomes, partially with a significance value of 0.000 < 0.05. (2) There is a positive and significant influence of learning motivation on student learning outcomes, partially with a significance value of 0.000 < 0.05. (3) There is a positive and significant influence between interest and learning motivation on student learning outcomes simultaneously with a significance value of 0.000 < 0.05.